Reading Guide - Redaktion, Peripeti (Peripeti, 2021)
Læsevejledning / Reading guide for Peripeti 33 Alle tema-artikler i det følgende nummer er fagfællevurderede. Disse er markeret med en * i titlerne. Essays og anmeldelser er ikke fagfællevurderede. All themed articles in the following issue of Peripeti have undergone peer review. These articles are marked with a * in their title. Essays and reviews have not undergone peer review.